Bcl9 Depletion Modulates Endothelial Cell in Tumor Immune Microenvironment in Colorectal Cancer Tumor - Wei, Zhuang; Feng, Mei; Wu, Zhongen; Shen, Shuru; Zhu, Di (Frontiers in Oncology, 2021)
Tumor endothelial cells are an important part of the tumor microenvironment, and angiogenesis inhibitory therapy has shown potential in tumor treatment. However, which subtypes of tumor endothelial cells are distributed in tumors, what are the differences between tumor endothelial cells and normal endothelial cells, and what is the mechanism of angiogenesis inhibitory therapy at the histological level, are all need to be resolved urgently. Using single-cell mRNA sequencing, we found that knockdown of the downstream factor BCL9 in the Wnt signaling pathway or inhibitor-mediated functional inhibition can modulate tumor endothelial cells at a relatively primitive stage, inhibiting their differentiation into further extracellular matrix construction and angiogenesis functions. Furthermore, we propose a BCL9-endo-Score based on the differential expression of cells related to different states of BCL9 functions. Using published data sets with normal endothelial cells, we found that this score can characterize endothelial cells at different stages of differentiation. Finally, in the TCGA pan-cancer database, we found that BCL9-endo-Score can well predict the prognosis of kidney cancer and a type of breast cancer, and identified the markers of these tumor subtypes. Our data also provides an important basis for tumor precision treatment with angiogenesis inhibitory therapy by targeting the Wnt signaling pathway.